Identification and risk assessment of human and veterinary antibiotics in the wastewater treatment plants and the adjacent sea in Tunisia - Tahrani, Leyla; Van Loco, Joris; Anthonissen, Roel; Verschaeve, Luc; Ben Mansour, Hedi; Reyns, Tim (Water science and technology, 2017)
In the following study, we came up with and validated a prompt, sensitive and precise method for the simultaneous determination of 56 antimicrobial drugs (tetracyclines, sulfonamides, β-lactams, macrolides and quinolones) using the ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). This method was implemented with success to determine antibiotics in samples collected from four wastewater treatment plants and five coasts in Tunisia. Results showed the presence of high concentrations of antibiotics that ranged from 0.1 to 646 ng mL−1, which can induce many negative impacts on health and the environment. For this reason, we have opted to evaluate toxicity of wastewater samples using a battery of biotests. In fact, genotoxicity was assessed using three tests: Vitotox, comet and micronucleus assays. The input and output of wastewater treatment plants induced a strongly genotoxic effect on the Salmonella typhimurium TA104 prokaryotic Vitotox assay. This result was confirmed using the comet and the micronucleus assays performed on the human liver hepatocellular carcinoma cells. The genotoxic power of the tested wastewater treatment plants' samples could be attributed to the presence of the higher quantities of antibiotics that are detected in these samples and to the antibiotic and organic compound cocktails.